Cannabinol (CBN; 30 and 300 mg) effects on sleep and next-day function in insomnia disorder (‘CUPID’ study): protocol for a randomised, double-blind, placebo-controlled, cross-over, three-arm, proof-of-concept trial - Ronald R Grunstein; Bandana Saini; Christopher J Gordon; Anastasia Suraev; Angela L D'Rozario; Chris Irwin; Camilla M Hoyos; Iain McGregor; Brendon Yee; Isobel Lavender; Danielle McCartney; Nathaniel Marshall (BMJ Open)
Objective Insomnia is the most prevalent sleep disorder, with few effective pharmacotherapies. Anecdotal reports and recent preclinical research suggest that cannabinol (CBN), a constituent of Cannabis sativa derived from delta-9-tetrahydrocannabinol, could be an effective treatment. Despite this, the isolated effects of CBN on sleep have yet to be systematically studied in humans.Methods The present protocol paper describes a randomised, double-blind, placebo-controlled, single-dose, three-arm, cross-over, proof-of-concept study which investigates the effects of CBN on sleep and next-day function in 20 participants with clinician-diagnosed insomnia disorder and an Insomnia Severity Index Score ≥15. Participants receive a single fixed oral liquid dose of 30 mg CBN, 300 mg CBN and matched placebo, in random order on three treatment nights; each separated by a 2-week wash-out period. Participants undergo overnight sleep assessment using in-laboratory polysomnography and next-day neurobehavioural function tests. The primary outcome is wake after sleep onset minutes. Secondary outcomes include changes to traditional sleep staging, sleep-onset latency and absolute spectral power during non-rapid eye movement (NREM) sleep. Tertiary outcomes include changes to sleep spindles during NREM sleep, arousal indices, absolute spectral power during REM sleep and subjective sleep quality. Safety-related and exploratory outcomes include changes to next-day simulated driving performance, subjective mood and drug effects, postural sway, alertness and reaction time, overnight memory consolidation, pre and post-sleep subjective and objective sleepiness; and plasma, urinary, and salivary cannabinoid concentrations. The study will provide novel preliminary data on CBN efficacy and safety in insomnia disorder, which will inform larger clinical trials.Ethics and dissemination Human Research Ethics Committee approval has been granted by Bellberry (2021-08-907). Study findings will be disseminated in a peer-reviewed journal and at academic conferences.Trial registration number NCT05344170.